HUBUNGAN POLA KOMUNIKASI KELUARGA DAN KEKUATAN KELUARGA DENGAN PENCEGAHAN PERILAKU SEKSUAL PRANIKAH PADA REMAJA DI SMAN 75 JAKARTA - Anggi Dwi Prasetyo (2021)
Adolescents are at risk of having premarital sexual behavior problems caused by the lack of family communication patterns and good family strengths in delaying sexual debut and preventing premarital sexual behavior. This study aims to determine the relationship of communication patterns of families and strength families with the prevention of adolescent premarital sexual behavior at SMAN 75 Jakarta. This type of research is quantitative with a cross sectional analytic descriptive approach. A sample of 147 adolescents using simple cluster sampling technique. Chi-square analysis results show that there is a significant relationship between communication patterns of families with the prevention adolescents premarital sexual behavior with P-value=0,000 and there is a strength families with the prevention adolescents premarital sexual behavior with P-value=0,002. Adolescents in order to avoid premarital sexual behavior are starting to build effective and open communication between parents and their children so that there is no embarrassment in communicating and teenagers can take part in school activities such as extracurricular.